Comparative analysis of opto-electronic performance of aluminium and silver nanoporous and nano-wired layers - Marus, Mikita (2016)
The comparison of optical and electronic properties between randomly and uniformly arranged nano-wired layers of silver and aluminium was presented. The random configuration possessed similar average transmittance in the visible wavelength range, when the quantity of nano-wires was increased from 2 to 20 per area of 8×8 μm2; and higher average transmittance up to 38% and 45% when the quantity of nano-wires was increased from 20 to 200 per area of 8×8 μm2 for silver and aluminium nano-wired layers, respectively. Insignificant difference of the transmittance for silver and aluminium nano-wired layers was observed when the open area was less or equal to 55% regarding of the configuration. This difference became considerable as the open area grew larger than 55%: the uniform and random silver nano-wired possess up to 15% and 5% higher transmittance in comparison to aluminium nano-wired layers, respectively.